E2F-1 overexpression inhibits human gastric cancer MGC-803 cell growth in vivo - Wei, Wei-Yuan (World J Gastroenterol, 2015)
AIM: To evaluate the influence of E2F-1 on the growth of human gastric cancer (GC) cells in vivo and the mechanism involved. METHODS: E2F-1 recombinant lentiviral vectors were injected into xenograft tumors of MGC-803 cells in nude mice, and then tumor growth was investigated. Overexpression of transcription factor E2F-1 was assessed by reverse transcription-polymerase chain reaction (RT-PCR) and Western blotting analysis. Apoptosis rates were determined using a terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) assay. Expression levels of certain cell cycle regulators and apoptosis-related proteins, such as Bax, survivin, Bcl-2, cyclin D1, S-phase kinase-associated protein 2, and c-Myc were examined by Western blotting and RT-PCR. RESULTS: Xenograft tumors of MGC-803 cells in nude mice injected with E2F-1 recombinant lentiviral vectors stably overexpressed the E2F-1 gene as measured by semi-quantitative RT-PCR (relative mRNA expression: 0.10 ± 0.02 vs 0.05 ± 0.02 for control vector and 0.06 ± 0.03 for no infection; both P < 0.01) and Western blotting (relative protein expression: 1.90 ± 0.05 vs 1.10 ± 0.03 in control vector infected and 1.11 ± 0.02 for no infection; both P < 0.01). The growth-curve of tumor volumes revealed that infection with E2F-1 recombinant lentiviral vectors significantly inhibited the growth of human GC xenografts (2.81 ± 1.02 vs 6.18 ± 1.15 in control vector infected and 5.87 ± 1.23 with no infection; both P < 0.05) at 15 d after treatment. TUNEL analysis demonstrated that E2F-1 overexpression promoted tumor cell apoptosis (18.6% ± 2.3% vs 6.7% ± 1.2% in control vector infected 6.3% ± 1.2% for no infection; both P < 0.05). Furthermore, lentiviral vector-mediated E2F-1 overexpression increased the expression of Bax and suppressed survivin, Bcl-2, cyclin D1, Skp2, and c-Myc expression in tumor tissue. CONCLUSION: E2F-1 inhibits growth of GC cells via regulating multiple signaling pathways, and may play an important role in targeted therapy for GC.